2011
DOI: 10.1093/brain/awq354
|View full text |Cite
|
Sign up to set email alerts
|

CD161highCD8+T cells bear pathogenetic potential in multiple sclerosis

Abstract: To identify differentially expressed genes in multiple sclerosis, microarrays were used in a stringent experimental setting-leukapheresis from disease-discordant monozygotic twins and gene expression profiling in CD4(+) and CD8(+) T-cell subsets. Disease-related differences emerged only in the CD8(+) T-cell subset. The five differentially expressed genes identified included killer cell lectin-like receptor subfamily B, member 1, also known as natural killer receptor protein 1a/CD161, presented by the Internati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
162
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 192 publications
(181 citation statements)
references
References 38 publications
16
162
1
1
Order By: Relevance
“…Moreover, all the circulating Tc17 cells are contained within this CD161 high subset, further suggesting a role for this subset of CD8 T cells in MS pathogenesis [46]. It is at present unclear whether these CD161 high CD8 T cells are conventional HLA class I-restricted T cells or whether they belong to an innate-like T cell subset.…”
Section: Cd8 T Cells and Their Subsets In Msmentioning
confidence: 97%
See 3 more Smart Citations
“…Moreover, all the circulating Tc17 cells are contained within this CD161 high subset, further suggesting a role for this subset of CD8 T cells in MS pathogenesis [46]. It is at present unclear whether these CD161 high CD8 T cells are conventional HLA class I-restricted T cells or whether they belong to an innate-like T cell subset.…”
Section: Cd8 T Cells and Their Subsets In Msmentioning
confidence: 97%
“…In contrast, inactive lesions contained only few IL-17-producing T cells [45]. Furthermore, Annibali et al have identified significant up-regulation of natural killer receptor protein 1a/CD161 and increased numbers of CD161 high CD8 T cells in the peripheral blood of MS patients [46]. This subset of CD8 T cells includes most of the CCR6+, effector memory T cells with pro-inflammatory properties.…”
Section: Cd8 T Cells and Their Subsets In Msmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, MAIT cells are also well established to be recruited to sites of inflammation,81, 125 and have been found to be enriched in the synovial fluid of patients with ankylosing spondylitis126 and RA127. They have also been shown to be recruited to the lung of patients with active tuberculosis infection,81, 82 increased in inflamed intestinal tissues in patients with inflammatory bowel disease,125 adipose tissues of obese patients,128 and are present in multiple sclerosis (MS) lesions 129, 130, 131. MAIT cell recruitment to inflamed tissues is further increased by their upregulation of chemokine receptors CXCR3, which binds IFN‐dependent ligands CXCL9/10/11 in inflamed tissues 118…”
Section: Functional Similarities Between Nk Cell and Cd8+ T‐cell Subsetsmentioning
confidence: 99%